Perbedaan tingkat pengetahuan tentang kesehatan reproduksi pada mahasiswa Fakultas Kedokteran, Fakultas Hukum dan Fakultas Ekonomi Universitas Palangka Raya - Panjaitan, Gabrielle Angelique; Adnyana, I Gde Hary Eka; Astrid Teresa; Natalia Sri Martani; Dian Mutiasari (Fakultas Kedokteran Universitas Palangka Raya, 2023)
Knowledge about sexual and reproductive health such as sexually transmitted infections has a huge influence all over the world. Seeing cases related to reproductive health in indonesia is still relatively high both among men and women. This study was conducted to see how different levels of knowledge in the field of reproductive health in students of the FK, FH and FE. This study uses descriptive Analytical Study type with cross sectional method. Data collection was done by using questionnaires that have been tested for validity and reliability, after that univariate analysis and data processing with computerization. This study obtained the results for, the level of knowledge of students of the FK is good 97.7%, students of the FH is good knowledge of 75.5%, while students of the FE are 55.4%. It can be concluded that there is a difference in the level of knowledge between the students of the FK, FH, and FE, where it can be seen that the best level of knowledge is the students of the FK, followed by students of the FH, and sufficient level of knowledge is the students of the FE.